Assam's District and Subdivisional Five Year Plan 1951-54 Naga Hills District - Government of Assam (Government of Assam, 1954)
The Assam District and Subdivisional Five-Year Plan (1951-54) for Naga Hills District outlines a comprehensive approach to district-level socio-economic development, focusing on agriculture, rural development, education, and health infrastructure. The plan categorizes initiatives under general state schemes, expansions, Article 275 for tribal areas, community projects, and local works, with a total allocation of 43.224 lakhs. By the end of the third year, only 19.30 lakhs had been expended, highlighting significant underutilization and the need for improved implementation efficiency. Agricultural programs emphasize minor irrigation and plant protection to enhance productivity, while rural development schemes promote self-help and economic independence. Investments in education include the establishment of basic facilities and scholarships, aligning with literacy enhancement objectives, and health initiatives aim to improve medical infrastructure and awareness. The plan also establishes Subdivisional Development Committees and Boards to foster local decision-making and community participation, encouraging ownership of development processes. Despite well-articulated goals, the plan identifies gaps in resource utilization, underscoring the importance of strengthened monitoring mechanisms and stakeholder collaboration. Overall, the Five-Year Plan provides a structured framework for addressing the Naga Hills District’s developmental needs, laying the foundation for sustainable growth and socio-economic advancement in Assam’s diverse districts.
Naga Hills District
Naga Hills District
Keywords: Assam Five-Year Plan; Naga Hills District; Socio-Economic Development; Tribal Areas; Agriculture; Rural Development; Education; Health Infrastructure; Community Projects; Local Works; Resource Allocation; Subdivisional Committees